Pengembangan Media Permainan Gerobak Sayur Untuk Meningkatkan Kecerdasaan Logika Matematika Anak Usia 5-6 Tahun di TK Al- Anwar Kota Bengkulu - Fitri Maya Sari (IAIN Bengkulu, 2022)
AbstractMathematical logic intelligence is one of the multiple intelligences that discusses numbers, counting, recognizing colors and shapes. So mathematical logic intelligence is one of the important things for children to have, therefore the aim of the researcher is to produce a product in the form of a vegetable cart game media to improve children's mathematical logic intelligence designed with numbers 1-10, counting additions, recognizing various kinds of kinds of vegetables, recognize the colors, shapes of vegetables, and find out if these are effective for increasing children's mathematical logic intelligence. This type of research used is Research and Development (R&D) Using the ADDIE Model which consists of five stages, namely analysis, design development, implementation, and evaluation. However, because the researchers adapted to the existing needs, the researchers tested the product on a small scale by being tested with 12 children. Based on the results of the research conducted on the development of the vegetable cart game media to improve the mathematical logic intelligence of children aged children, the results of the Pre-test activity sheets were 39.62%. Meanwhile, on the post-test activity sheet it was 94.01%. Thus there was an increase of 54.95%. So it can be concluded that the product of the vegetable cart game media development to improve the mathematical logic intelligence of children aged 5-6 years in Al-Anwar Kindergarten, Bengkulu City is feasible to use. Keywords: Vegetable cart game media, mathematical logic intelligence